Computer-Based Interactive Project E-book: A Guide for Genetic 1 Course to Enhance Biology Students’ Cognitive Learning Results - Hikmah Buroidah; Siti Zubaidah; Susriyati Mahanal; Azizul Ghofar Candra Wicaksono (Graduate School of Universitas Negeri Malang, 2022)
This study aims to develop a computer-based interactive Genetics project guide e-book to enhance undergraduate biology students’ cognitive learning outcomes. This development was carried out because there had been no available written guidebook for the Genetics project, which resulted in non-optimum project implementation. The content in the e-book consists of a description of material related to Drosophila melanogaster, descriptions and videos of general procedures, PjBL-based learning activities, and quizzes. Lee and Owen’s development model was used in this study which consisted of 4 stages, (1) multimedia need assessment and analysis; (2) multimedia instructional design; (3) multimedia development and implementation; and (4) multimedia evaluation. Before being implemented, the e-book was validated by material experts, learning media experts, and Genetics lecture. The effectiveness of the e-book in enhancing cognitive learning outcomes was measured using the ANCOVA test. The results of the e-book effectiveness test showed a significant difference between the control and experimental classes. These results indicate that the computer-based interactive e-book is valid, practical, and effective for use in the learning process of the Genetics project.